Bacterial detection at multiple locations at a university health sciences center (Research, Society and Development, 2020)
The objective of this study was to verify the level of infection by microorganisms in a health sciences university campus of a reference university. The collections were performed in December 2018 at the Faculty of Medical Sciences of the State University of Piaui. Four swabs were initially immersed in saline in Falcon tubes and then gently passed on the surface of four different places: ramp handrail, library men's bathroom handle, academic center handle and seat from the academic center. After passing the swabs on their respective surfaces, they were returned to the Falcon tubes with saline and taken to the laboratory for analysis. With sowing and cultivation, it was observed that only the doorknob of the academic center and the handrail presented significant levels of bacteria. Observing the colonies under the light microscope, it was found that on the doorknob there were colonies of gram negative bacilli and gram positive cocci, which is an indication of the presence of S.aureus and E.coli. In the handrail, there was a strong presence of gram positive bacilli, but gram negative bacilli and gram positive cocci were also observed. Further study in order to better describe the strains in the health center studied would be important to understand the real risks that people in this environment are running. In addition, investment in antiseptic techniques such as gel alcohol and biosecurity techniques such as the correct storage of equipment used in hospitals and taken to college, such as a lab coat and a stethoscope, is extremely necessary.